On illegal killings of wildlife in Fennoscandia - Von Essen, Erica; Nordström Källström, Helena; Hansen, Hans Peter; Peterson, M. Nils; Peterson, Tarla R. (2017)
Rising levels of discontent among rural residents and parts of the hunting community toward large carnivore conservation policy has effected a phenomenon of socio-politically motivated illegal killing of these unpopular species. Such wildlife crime formed the investigation of an interdisciplinary and internationally collaborative research project headed by the Swedish University of Agricultural Sciences in Ultuna, Uppsala. Through 3 years of in-depth interview studies with hunters in Sweden, a quantitative survey to hunters, comparative studies in other parts of the world and close collaboration with Fennoscandian researchers and practitioners, this project ran to completion at the end of 2016. The following report marks the dissemination and discussion of the research results and insights for future research produced by this project. Hence, it represents the first time the full research project and its members stand before the public and interest groups. The report synthesizes two days of workshop thematic discussions between 45 participants from societal sectors including hunting and nature conservation NGOs, county administrative boards, Environmental Protection Agencies, law enforcement, environmental attorneys and farming associations as they feature across the Fennoscandian countries: Sweden, Norway, Denmark and Finland. Its discussions center on social control in wildlife crime, the juridification of hunting issues, the influence of the EU and platforms for going forward to mitigate poaching, in particular of large carnivores like the wolf. The report is an essential read for both researchers and practitioners faced with the problem of socially accepted, but secretive and hidden, forms of illegal hunting in response to governmental legitimacy crises, distrust of policy and policy-makers, and as a manifestation of rural resistance in modernity.